Noise Reduction on The Use of Different Ground Model on The EMI Filter of Reading LED Lighting for Passenger Train - Haryo Dwi Prananto; Muhammad Imam Sudrajat; Priyo Wibowo; Yoppy Yoppy; R. Harry Arjadi (Jurusan Teknik Elektro Universitas Andalas, 2020)
Initial measurement showed that reading LED lighting used in this experiment produced excessive conducted emissions (CE). EMC filter is needed to suppress the CE noise. The LED light is AC powered through a two-wire cable without ground wire, whereas the EMC filter does have ground. Experiments were conducted to find out the attenuation effect of different filter’s grounding connection methods. Four cases of grounding connections are measured and compared, i.e. unconnected ground, earth-connected ground, chassis-connected ground, and additional ground plate. Measurements showed that chassis-connected ground had the strongest attenuation effect. Also, for the additional ground plate configuration, it turned out that larger plates exhibited stronger attenuation compared to smaller plates.Keywords : LED driver, EMC Filter, grounding, impedance, common mode